2010
DOI: 10.3354/meps08277
|View full text |Cite
|
Sign up to set email alerts
|

Association of the stramenopilan protists, the aplanochytrids, with zooplankton of the equatorial Indian Ocean

Abstract: Thraustochytrids and aplanochytrids, belonging to the Labyrinthulomycetes of the Kingdom Stramenopila, have been frequently reported to occur as parasites or symbionts in a number of coastal invertebrates. Given the fact that these protists are widespread in coastal and oceanic waters, it is possible that they are also associated with pelagic zooplankton. This study examines their occurrence in zooplankton from equatorial waters of the Indian Ocean. A total of 171 of 2100 individual specimens of zooplankton yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 48 publications
2
44
0
Order By: Relevance
“…These results suggest that Aplanochytrium is a geographically widespread genus with restricted phylogenetic diversity. Damare & Raghukumar (2006) recently suggested that aplanochytrids might be more abundant than thraustochytrids in open-ocean waters. The group of environmental sequences named uLa8 may represent either a novel species of Aplanochytrium or a novel related genus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results suggest that Aplanochytrium is a geographically widespread genus with restricted phylogenetic diversity. Damare & Raghukumar (2006) recently suggested that aplanochytrids might be more abundant than thraustochytrids in open-ocean waters. The group of environmental sequences named uLa8 may represent either a novel species of Aplanochytrium or a novel related genus.…”
Section: Discussionmentioning
confidence: 99%
“…Aplanochytrids have been isolated from a variety of plant, algal, and animal substrates as well as sediment and seawater samples collected in polar, temperate, and tropical habitats (e.g. Leander et al 2004, Damare & Raghukumar 2006. In addition to the 18S-F/LABY-Y amplicon sequences recovered from Peconic Bay, Port Jefferson Harbor, and Long Island Sound sediment samples and a Peconic Bay seawater sample, 18S rDNA sequences very similar to cultivated aplanochytrids have been recovered in universal 18S rDNA libraries constructed from a variety of sediment (including arctic and hydrothermal areas) and seawater samples (including normoxic Mediterranean surface seawater and the suboxic part of the Cariaco Basin water column) (Edgcomb et al 2002, Stoeck et al 2003, Massana et al 2004a,b, Zuendorf et al 2006.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, none of the aplanochytrids from the zooplankton of oceanic waters produced chitinase, indicating that they may not significantly degrade zooplankton exoskeletons (Damare and Raghukumar, 2006). Members of Labyrinthulomycetes appear to be highly efficient in degrading protein.…”
Section: Labyrinthulomycetes As Remineralizers In the Ecosystemmentioning
confidence: 99%
“…Thraustochytrids secrete a wide variety of extracellular enzymes in vitro, such as proteases, lipases, cellulases, amylases, xylanases, gelatinase, urease, phosphatase, chitinase and α-Glucosidase , Bremer and Talbot 1995, Bongiorni et al 2005b, Damare and Raghukumar 2006, Taoka et al 2009, Nagano et al 2010). …”
Section: Labyrinthulomycetes As Remineralizers In the Ecosystemmentioning
confidence: 99%